National Agriculture Rural Inclusive Growth Project (NARIGP) Climate Risk Profiles Validation Workshop Presentation - Kinyua, Ivy Wambui (Bioversity International and the International Center for Tropical Agriculture, 2021)
The Government of Kenya (GoK) is implementing the National Agricultural and Rural Inclusive Growth Project (NARIGP) with support from the World Bank. The project is being implemented through the Ministry of Agriculture, Livestock, Fisheries, and Cooperatives. The project's objective is to boost agricultural productivity and profitability in selected rural communities. To assess the risks and vulnerabilities associated with climate change, which have a negative impact on agricultural production, the Alliance of Bioversity International and the International Center for Tropical Agriculture (CIAT) were commissioned to conduct a climate risk assessment. The assessment's objective is to provide information about the current climate and possible future climate scenarios, to identify climate-related vulnerabilities and risks for major agricultural value chains and specific groups of people involved in agriculture, to identify adaptation options that address climate risks and vulnerabilities, and to assess institutional capacity to deal with climate risks and vulnerabilities.These climate risk profiles are intended to inform county governments and stakeholders about the risks and opportunities associated with climate change for agriculture.